Marcia Hafif- The Inventory: Painting - Hafif, Marcia; Holte, Michael Ned; McFadden, Jane (Laguna Art Museum; California State University, Fullerton; Grand Central Press, 2015)
Preface by Ines Goldbach, Roland Waspe. Text by Jane McFadden, Marcia Hafif. Interview by Michael Ned Holle. American artist Marcia Hafif (born 1929) helped radicalize painting in the 1970s with her monochrome works and drawings, gathered under the auspice of what she calls (3z(BThe Inventory.(3y (BThis volume documents one series, the Black Paintings.s
English
Keywords: 21st century; N4390-5098 Visual Arts. Exhibitions